A numerical model for permeability of cement mortar considering the interfacial transition zone. Issue 1 (12th January 2021) - Han, Xun; Ren, Mingqian; An, Xuehui; Liu, Zuguang; Nie, Ding
Abstract : A numerical model for evaluating the permeability of cement mortar is proposed. The numerical model simulates the permeation process of cement mortar under water pressure considering the cement paste connectivity and the connectivity of interfacial transition zone (ITZ). To illustrate the connectivity of the ITZ, a critical volume fraction of fine aggregates is proposed to indicate the threshold at which percolation of the ITZ occurs in the mortar penetration process. The numerical model was validated using empirical experimental results of a series of water penetration pressure tests. The phenomena in which the permeability ratio increases with the volume fraction of aggregate and a dramatic increase appears at a volume content of 35–45% are explained through the interconnection and percolation of ITZs. Finally, using the proposed numerical model, the influence of the ITZ on vapour water permeability is evaluated, which shows that the ITZ effect has very little influence on vapour moisture transport.